2022
DOI: 10.3390/curroncol29060312
|View full text |Cite
|
Sign up to set email alerts
|

Trop-2 in Upper Tract Urothelial Carcinoma

Abstract: Trophoblast cell surface antigen 2 (Trop-2, encoded by TACSTD2) is the target protein of sacituzumab govitecan, a novel antibody-drug conjugate for locally advanced or metastatic urothelial carcinoma. However, the expression status of Trop-2 in upper tract urothelial carcinoma (UTUC) remains unclear. We performed immunohistochemical analysis of 99 UTUC samples to evaluate the expression status of Trop-2 in patients with UTUC and analyze its association with clinical outcomes. Trop-2 was positive in 94 of the 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Similarly, in our data, Trop-2 positivity rates did not differ significantly among the UTUC subtypes (Table 2). In our previous study (54), high Trop-2 expression was associated with a good prognosis in UTUC, and the findings also confirmed that the high TASCSTD2 expression group still showed a favorable prognosis in gene expression analysis using RNA sequencing data. These findings were inconsistent with those reported for UBC; high Trop-2 expression was associated with increased tumor aggressiveness and poor prognosis.…”
Section: Trop-2supporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, in our data, Trop-2 positivity rates did not differ significantly among the UTUC subtypes (Table 2). In our previous study (54), high Trop-2 expression was associated with a good prognosis in UTUC, and the findings also confirmed that the high TASCSTD2 expression group still showed a favorable prognosis in gene expression analysis using RNA sequencing data. These findings were inconsistent with those reported for UBC; high Trop-2 expression was associated with increased tumor aggressiveness and poor prognosis.…”
Section: Trop-2supporting
confidence: 76%
“…Therefore, evaluation of the expression of Trop-2 in solid tumors is clinically important to predict the efficacy of sacituzumab govitecan. The Trop-2-positive rate in UTUC was found in 94% (94/99) of UTUC cases in our previous study (54), while it was reported to be 83% in UBC (53). This finding suggests that UTUC also has a high Trop-2-positivity rate and is a treatment option for advanced UTUC and UBC.…”
Section: Trop-2mentioning
confidence: 62%
See 1 more Smart Citation
“…It is highly expressed in multiple cancers, including urothelial carcinoma, with several studies reporting expression rates greater than 90%. 64 , 65 High TROP2 expression levels in advanced cancers portend a poor prognosis. In UC, TROP2 expression has been reported as being higher than that of nectin-4, indicating its suitability as a target for an ADC treating bladder cancer 66 ( Table 3 ).…”
Section: Trop2 Targeting Therapiesmentioning
confidence: 99%
“…Expression on these normal epithelial cells is at a much lower level than in epithelial tumors, making Trop-2 an ideal therapeutic target [ 1 , 2 , 3 ]. When Trop-2 is overexpressed, it acts as an oncogene promoting tumor proliferation, growth, invasion, and metastasis in epithelial cancers such as breast, colon, prostate, pancreatic, urothelial, and lung [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. High Trop-2 expression is associated with a poor prognosis in multiple cancer types, with worse overall survival and disease-free survival outcomes [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%